STUDI TERHADAP RETENSI KARYAWAN DI PT.HHK SUNGAI JELAI ESTATE, KABUPATEN KETAPANG - Tia Putri Ulandari; Agung Sedayu; Aris Puji Purwatiningsih; Nanda Adhi Purusa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the influence of leadership style, work environment, and compensation on employee retention at PT HHK Sungai Jelai Estate. Methods: This study involved 100 employees as samples. Data collection was carried out by distributing questionnaires, while the data analysis technique used was multiple linear regression. Results: The results of the study prove that leadership style, work environment, and compensation have a positive and significant influence on employee retention, with the work environment being the most dominant factor. Keywords: Compensation, Employee Retention, Leadership Style, Work Environment